Hubungan waktu tunggu dan length of stay (LOS) Dengan kepuasan pasien di instalasi Gawat darurat rsud jombang - Siti Maghfiroh; Ratna Puji Priyanti; Alik Septian Mubarrok (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Introduction: Waiting time and length of stay ( LOS ) is one of indicators the quality of service in emergency room (ER ) that affects satisfaction patients, where speed and the accuracy is the essence service in ER. Research aims to understand the relations of waiting time and LOS with satisfaction patients in of emergency room Jombang general hospital. Method: This research using correlational design with cross sectional approached. The technique sampling is accidental sampling. The population were 1.204 people. And the sample size 60 people. Data collection used a questionnaire for measuring satisfaction patients and observation stopwatch a use for measuring waiting time and LOS. Data analyzed by statistical tests the spearman rank. Result: The results of the study obtained 31 people ( 51.7 % ) of respondents with waiting time slow, 24 people ( 40,0 % ) of respondents with los slow, while for the satisfaction of patients 31 people ( 51.7 % ) of a patient is satisfied with service. Statistical tests the spearman rank showsed that waiting time with satisfaction obtained r value = 0,666, p value = 0,000. To LOS with satisfaction the r value = 0,350, p value = 0,006. There is a significant relation exists between waiting time and LOS with satisfaction patients. Discussion: Waiting time and LOS significant correlated with satisfaction patients in ER Jombang general hospital. The ER in Jombang general hospital is expected to have strong commitment, to give priority to the quality of service and interests of patients. Health workers is expected to give rapid service, right and respond to the problem of patients. And advanced research required about satisfaction patients in ER and the supporting factors.